The recent advances in vaccine adjuvants - Jiayin Xing; Xiangxiang Zhao; Xiaotian Li; Ren Fang; Mingrui Sun; Yang Zhang; Ningning Song (Frontiers in Immunology)
Vaccine adjuvants, as key components in enhancing vaccine immunogenicity, play a vital role in modern vaccinology. This review systematically examines the historical evolution and mechanisms of vaccine adjuvants, with particular emphasis on innovative advancements in aluminum-based adjuvants, emulsion-based adjuvants, and nucleic acid adjuvants (e.g., CpG oligonucleotides). Specifically, aluminum adjuvants enhance immune responses through particle formation/antigen adsorption, inflammatory cascade activation, and T-cell stimulation. Emulsion adjuvants amplify immunogenicity via antigen depot effects and localized inflammation, while nucleic acid adjuvants like CpG oligonucleotides directly activate B cells and dendritic cells to promote Th1-type immune responses and memory T-cell generation. The article further explores the prospective applications of these novel adjuvants in combating emerging pathogens (including influenza and SARS-CoV-2), particularly highlighting their significance in improving vaccine potency and durability. Moreover, this review underscores the critical importance of adjuvant development in next-generation vaccine design and provides theoretical foundations for creating safer, effective adjuvant.